Fe-phosphates in Jezero Crater as evidence for an ancient habitable environment on Mars - T. V. Kizovski; M. E. Schmidt; L. O’Neil; M. W. M. Jones; N. J. Tosca; D. A. Klevang; J. A. Hurowitz; C. T. Adcock; E. M. Hausrath; K. L. Siebach; Z. U. Wolf; S. Sharma; et al. (Nature Communications)
Abstract Phosphorus is an essential component for life, and in-situ identification of phosphate minerals that formed in aqueous conditions directly contributes toward one of the main goals of the Mars 2020 Perseverance rover: to seek signs of ancient habitable environments. In Jezero crater, proximity science analyses within a conglomerate outcrop, “Onahu” demonstrate the presence of rare Fe3+-bearing phosphate minerals (likely metavivianite, ferrolaueite, (ferro)beraunite, and/or santabarbaraite) embedded in a carbonate-rich matrix. While Fe-phosphates have been inferred previously on Mars, this work presents the most definitive in-situ identification of martian Fe-phosphate minerals to date, using textural, chemical, spectral, and diffraction analyses of discrete green-blue grains. The Fe-phosphate minerals’ textural context along with comparisons to Earth analogs suggest they likely formed after oxidation of Fe2+-phosphate vivianite, the most common Fe-phosphate in sedimentary environments on Earth, often associated with microbial activity and organics. While there is no obvious evidence of biological inputs in Onahu, if the Fe-phosphates’ formation environment was similar to vivianite-rich sedimentary environments on Earth, these minerals likely originally precipitated in conditions favorable to potential martian life — in a low temperature, reducing aqueous medium with high concentrations of bio-limiting elements, and Fe-redox gradients that could provide an energy source. If the sample collected from Onahu (Otis_Peak) is returned to Earth, analysis of the Fe-phosphates may provide new insights into ancient habitable environments on Mars.